The representation of sneakerhead culture in Sneaker Freaker magazine - Nurbaity; Mangaraja, Andreas (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2021)
This study aims to analyze the representation of sneakerhead culture in Sneaker Freaker Magazine using the circuit of culture theory. The descriptive-analytical methodology is applied to analyze the elements of sneakerhead culture based on characteristics, behaviors, and sneaker as a commodity manifested in sneakerhead culture. In order to complete this study, the researcher adds sneakerhead culture figures as the representation in the analysis. This study shows that the representation of sneakerhead culture in Sneaker Freaker Magazine can be seen by the reflected meaning and constructed meaning through object representation as a unique culture. The representation reflects communities' lifestyle, characteristics, commitment, and behaviors in sneakerhead culture to deliver the constructed meaning and identity.